Comparison of in-hospital and out-of-hospital cardiac arrest of trauma patients in Qatar - Furqan B. Irfan (13359828) (2022)
Background Cardiac arrests in admitted hospital patients with trauma have not been described in the literature. We defined “in-hospital cardiac arrest of a trauma” (IHCAT) patient as “cessation of circulatory activity in a trauma patient confirmed by the absence of signs of circulation or abnormal cardiac arrest rhythm inside a hospital setting, which was not cardiac re-arrest.” This study aimed to compare epidemiology, clinical presentation, and outcomes between in- and out-of-hospital arrest resuscitations in trauma patients in Qatar. It was conducted as a retrospective cohort study including IHCAT and out-of-hospital trauma cardiac arrest (OHTCA) patients from January 2010 to December 2015 utilizing data from the national trauma registry, the out-of-hospital cardiac arrest registry, and the national ambulance service database. Results There were 716 traumatic cardiac arrest patients in Qatar from 2010 to 2015. A total of 410 OHTCA and 199 IHCAT patients were included for analysis. The mean annual crude incidence of IHCAT was 2.0 per 100,000 population compared to 4.0 per 100,000 population for OHTCA. The univariate comparative analysis between IHCAT and OHTCA patients showed a significant difference between ethnicities (p=0.04). With the exception of head injury, IHCAT had a significantly higher proportion of localization of injuries to anatomical regions compared to OHTCA; spinal injury (OR 3.5, 95% CI 1.5–8.3, p<0.004); chest injury (OR 2.62, 95% CI 1.62–4.19, p<0.00), and abdominal injury (OR 2.0, 95% CI 1.0–3.8, p<0.037). IHCAT patients had significantly higher hypovolemia (OR 1.66, 95% CI 1.18–2.35, p=0.004), higher mean Glasgow Coma Scale (GCS) score (OR 1.4, 95% CI 1.3–1.6, p<0.00), and a greater proportion of initial shockable rhythm (OR 3.51, 95% CI 1.6–7.7, p=0.002) and cardiac re-arrest (OR 6.0, 95% CI 3.3–10.8, p=<0.00) compared to OHTCA patients. Survival to hospital discharge was greater for IHCAT patients compared to OHTCA patients (OR 6.3, 95% CI 1.3–31.2, p=0.005). Multivariable analysis for comparison after adjustment for age and gender showed that IHCAT was associated with higher odds of spinal injury, abdominal injury, higher pre-hospital GCS, higher occurrence of cardiac re-arrest, and better survival than for OHTCA patients. IHCAT patients had a greater proportion of anatomically localized injuries indicating solitary injuries compared to greater polytrauma in OHTCA. In contrast, OHTCA patients had a higher proportion of diffuse blunt non-localizable polytrauma injuries that were severe enough to cause immediate or earlier onset of cardiac arrest. Conclusion In traumatic cardiac arrest patients, IHCAT was less common than OHTCA and might be related to a greater proportion of solitary localized anatomical blunt injuries (head/abdomen/chest/spine). In contrast, OHTCA patients were associated with diffuse blunt non-localizable polytrauma injuries with increased severity leading to immediate cardiac arrest. IHCAT was associated with a higher mean GCS score and a higher rate of initial shockable rhythm and cardiac re-arrest, and improved survival rates. Other Information Published in: International Journal of Emergency Medicine License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12245-022-00454-0